2020
DOI: 10.1101/2020.06.30.180778
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structural basis of TRPC4 regulation by calmodulin and pharmacological agents

Abstract: ABSTRACTCanonical transient receptor potential channels (TRPC) are involved in receptor-operated and/or store-operated Ca2+ signaling. Inhibition of TRPCs by small molecules was shown to be promising in treating renal diseases. In cells, the channels are regulated by calmodulin. Molecular details of both calmodulin and drug binding have remained elusive so far. Here we report structures of TRPC4 in complex with a pyridazinone-based inhibitor and a pyridazin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 73 publications
(81 reference statements)
0
10
0
Order By: Relevance
“…Recently, two distinct inhibitor binding sites were identified in the hTRPC6 channel (Bai et al, 2020a;Tang et al, 2018b). During the editorial process of this work, inhibitor binding sites were also identified in TRPC4 (Vinayagam et al, 2020) and TRPC5 (Wright et al, 2020). Together with the sites identified in this study, we classify them into three groups, namely inhibitor binding pocket (IBP) A-C ( Figure 6, Figure 6-figure supplement 1).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Recently, two distinct inhibitor binding sites were identified in the hTRPC6 channel (Bai et al, 2020a;Tang et al, 2018b). During the editorial process of this work, inhibitor binding sites were also identified in TRPC4 (Vinayagam et al, 2020) and TRPC5 (Wright et al, 2020). Together with the sites identified in this study, we classify them into three groups, namely inhibitor binding pocket (IBP) A-C ( Figure 6, Figure 6-figure supplement 1).…”
Section: Discussionmentioning
confidence: 76%
“…GFB-8438, GFB-9289 and GFB-8749 are piperazinone/pyridazinone derivatives that inhibit TRPC4 and TRPC5 channels. Structure of zebrafish TRPC4 in complex with these inhibitors showed they also bind inside VSLD (Vinayagam et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The initial finding of the Mike Zhu group that Ca 2+ -calmodulin binds to and inhibits all TRPC channels has been recently confirmed by the yet unpublished data from the Raunser group (the preprint of their upcoming article is available for preview at the bioRxive Preprint Server for Biology [ 109 ]). The Raunser group structural data refined the position of the calmodulin binding site on Danio rerio TRPC4 to residues 688–703 ( Figure 5 ).…”
Section: Structure Of Trpc Channelsmentioning
confidence: 99%
“…Initially, a slightly longer stretch of the CIRB domain (695–724 residues) on the mouse TRPC4’s C-terminus was identified using molecular biological and biochemical approaches by the Zhu laboratory [ 44 ]. The new TRPC4 structure data suggest that residues 704–725 are engaged in the Danio rerio TRPC4 protein core and should be inaccessible for calmodulin binding [ 109 ]. Vinayagam et al reported that Ca 2+ -calmodulin binds to the tip of the rib helix ( Figure 5 ) and that this results in the stabilization of the residues in and around the voltage-sensor-like domain which connects to the TRPC4 low gate, thus locking the gate [ 109 ].…”
Section: Structure Of Trpc Channelsmentioning
confidence: 99%
“…Automated data processing does not necessarily aim at the highest possible resolution. However, resolutions at 3-4 Å already allow identifying the position of small molecules in the binding pocket of a protein, especially when ligand-free highresolution structures are available as exemplified by previous data of the TRPC4 channel and actin filaments 4,5 . Consequently, automated processing especially facilitates the effective screening of many drug candidates.…”
mentioning
confidence: 99%